Abu Ja’far Al-Tahawi’s Views on The Attributes of God - In The Framework of Al-Aqida Al-Tahawiyya - - GÖKALP, Yusuf; TASHMATOV, Sultanbek (Scientific Journal of Faculty of Theology, 2021)
Among the works written in the field of Credal sciences, Abu Ja‘far al-Tahâwî’s Aqidah has an important place in Islamic thought and theology. This work in question has a great importance in terms of continuing the tradition of Hanafi thought and contributing to the formation of the Ahl-Sunnah creed. In this work, known as al-Aqida al-Tahâwiyya, various kalam issues, especially the subject of tawhid, are discussed. In this work, which is a continuation of the views of Abu Hanifa and his students, the basic theological views of Ahl al-Sunnah are explained with short, plain and understandable expressions. This work, which deals with the unity of Allah, His essence and attributes, as well as prophecy, destiny, creation of the Quran and human actions, has been followed by the later Sunni kalam scholars. In this article, after briefly mentioning Abu Jafar al-Tahawi’s life, works and sectarian identity, we will try to reveal his views on Allah’s attributes.